VARIANT OF ACCESSORY QUADRATE LOBE AND FISSURES IN THE LIVER AND THEIR CLINICAL CORRELATION - Iv. Maslarski (Trakia Journal of Sciences)
There are numerous variations in the human body, especially when considering blood vessels or peripheral nerves. Regarding the liver, the variations tend to occur in the vessels or ducts, whereas variations with the liver lobes are a rare phenomenon. The presence of an additional lobe or different compartments outside the norm can be due to embryological heteroplasia, which has a congenital origin. They can also be a consequence of a surgical intervention, compression of neighbouring organs or an increased volume of the diaphragm. Sometimes there are cases where other enlargements are mistaken for extra liver compartments for example enlarged lymph nodes, presence of liver cysts or haematoma or even build-up of fluids in the region of certain fissures. This finding was discovered in a routine dissection with medical students in Medical Faculty of SU “St. Kliment Ohridski”. What can be seen is accessory quadrate lobe (AQL), some fissures or sulci on the anterosuperior surface of the liver. The case mentioned above, is a rare phenomenon, as it occurs in under 10% of the human population and has a clinical significance regarding: diagnosis, surgery and transplantation. Awareness of this variation type will help avoid diagnostic errors and avoid complications or a fatal outcome.